2021
DOI: 10.3390/foods10091998
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review on Maillard Reaction Based on Milk Proteins and Carbohydrates in Food and Pharmaceutical Products: Advantages, Disadvantages, and Avoidance Strategies

Abstract: Milk has two main components that have high nutritional value—milk protein (casein and whey protein), and lactose. These components are extensively used in various areas, especially in food, i.e., as sweeteners, stabilizers, functional food ingredients, nutritional fortifiers, etc. Non-enzymatic browning refers to a series of chemical reactions between sugars and proteins that make food more appetizing. Non-enzymatic browning reactions include degradation of ascorbic acid, lipid peroxidation, caramel reaction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 126 publications
2
24
0
3
Order By: Relevance
“…At the same time, due to the stimulation of anesthetics, traction and other factors, patients are very likely to suffer from inhibition of gastrointestinal peristalsis after surgery, which in turn leads to symptoms of gastrointestinal dysfunction, such as non-flatus, non-defecation and abdominal distension. This may affect the surgical effect and rehabilitation process of patients (17)(18)(19). This study showed that the patients in the operating room nursing group had lower anal exhaust time, first defecation time, and gastric tube removal time than those in the conventional nursing group.…”
Section: Discussionmentioning
confidence: 71%
“…At the same time, due to the stimulation of anesthetics, traction and other factors, patients are very likely to suffer from inhibition of gastrointestinal peristalsis after surgery, which in turn leads to symptoms of gastrointestinal dysfunction, such as non-flatus, non-defecation and abdominal distension. This may affect the surgical effect and rehabilitation process of patients (17)(18)(19). This study showed that the patients in the operating room nursing group had lower anal exhaust time, first defecation time, and gastric tube removal time than those in the conventional nursing group.…”
Section: Discussionmentioning
confidence: 71%
“…2-ethylfuran and 2-pentylfuran are considered to have a meaty and caramel flavor, and methylpyrazine has a barbecue flavor, both of which can be obtained by the Maillard reaction [ 57 ]. Their higher detection intensities in back-pressure sterilized D. maruadsi surimi products (BAC) may be due to the combination of the higher moisture content and the heat treatment temperature (110 °C) which facilitates the Maillard reaction [ 68 ]. This also resulted in higher detection intensity for all other types of volatile compounds in BAC.…”
Section: Resultsmentioning
confidence: 99%
“…In ryazhenka, the presence of furfuryl alcohol (possessing a distinctive burnt caramel flavor) as well as the abundance of ketones, can be attributed to the baking process that initiates the Maillard reaction in milk [ 51 ]. It should be noted that, except for furfuryl alcohol, there were no other products of the Maillard reaction (i.e., 2,5-dimethyl-4-hydroxy-3(2H)-furanone and 2-methylbutyric acid/2-methyl-3-(methyldithio)furan) with a caramel flavor detected in ryazhenka, in contrast to the ryazhenka-like product [ 47 ].…”
Section: Resultsmentioning
confidence: 99%